Comparison of two soft tissue substitutes for the treatment of gingival recession defects: an animal histological study - Fernando Suárez-López Del Amo; Juan C. Rodriguez; Farah Asa'ad; Hom-Lay Wang
Abstract Objectives: This study aimed to compare two different soft tissue replacement grafts in their ability to treat gingival recession defects and successfully integrate with the surrounding tissues. Methodology: Nine beagle dogs were included and followed up to 10 weeks. Sites for intervention were allocated to one of the grafting materials investigated. Treatment consisted of coronally advanced flap combined with one of the two soft tissue substitutes on a previous surgically created defect. Materials employed were porcine-derived acellular dermal matrix (ADM) [Novomatrix™ (Test)] and collagen-based matrix (CBM) [Mucograft® (Control)]. Animals were sacrificed at 2, 6, and 10 weeks postoperatively and compared using descriptive histology and histomorphometric outcomes. Results: Macroscopic findings were similar between test and control groups at all intervals. After 10 weeks, both groups demonstrated successful incorporation of the grafting materials without signs of rejection and with comparable tissue integration. The histomorphometric data were similar between groups at 2 weeks; however, the test group provided greater root coverage and increase in tissue thickness than the control at 6- and 10-weeks post surgically. Conclusions: Both porcine-derived ADM and CBM revealed similar histological outcomes with successful integration and absence of adverse events. Test group provided superior outcomes regarding root coverage and increase in tissue thickness.